Children's mathematics: cognitively guided instruction - Carpenter, Thomas páginas
Cognitively Guided Instruction (CGI) is based on an integrated program of research focused on the development of students' mathematical thinking; on instruction that influences that development; on teachers' knowledge and beliefs that influence their instructional practices; and on the way that teachers' knowledge, beliefs, and practices are influenced by their understanding of students' mathematical thinking.This book is about helping teachers help students make sense of mathematics